2010
DOI: 10.1021/jp1095079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anchoring Group Position on Formation and Conductance of a Single Disubstituted Benzene Molecule Bridging Au Electrodes: Change of Conductive Molecular Orbital and Electron Pathway

Abstract: We investigated the effect of anchoring group position on the formation and electric conductance of single molecule junctions for benzenedithiol and benzenediamine by the scanning tunneling microscope break junction technique. The conductances of the single 1,4-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenediamine, and 1,3-benzenediamine molecules were 0.005 (±0.001) G 0 (G 0 = 2e 2/h), 0.004 (±0.001) G 0, 0.01 (±0.003) G 0, and 0.005 (±0.002) G 0, respectively. No 1,2-disubstituted benzene molecules formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
103
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 42 publications
5
103
1
Order By: Relevance
“…5,7,[20][21][22][23][24][25][26][27][28][29] In the former, a gold nano-contact is created by stretching a gold wire and, just before rupture, a solution containing the target molecules is added to the system. Subsequently, the metallic contact is further stretched until rupture and in some cases the molecules remain trapped between the Au-Au tips forming the molecular junctions.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,[20][21][22][23][24][25][26][27][28][29] In the former, a gold nano-contact is created by stretching a gold wire and, just before rupture, a solution containing the target molecules is added to the system. Subsequently, the metallic contact is further stretched until rupture and in some cases the molecules remain trapped between the Au-Au tips forming the molecular junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their small size (on the scale of Angstroms) and the large energy gaps (on the scale of eV), transport through single molecules can remain phase coherent even at room temperature, and constructive or destructive quantum interference (QI) can be utilized to manipulate their room temperature electrical [10][11][12][13] and thermoelectrical 14,15 properties. In previous studies, it was reported theoretically and experimentally that the conductance of a phenyl ring with meta (m) connectivity is lower than the isomer with para (p) connectivity by several orders of magnitude [16][17][18][19][20][21][22][23][24][25] . This arises because partial de Broglie waves traversing different paths through the ring are perfectly out of phase leading to destructive QI in the case of meta coupling, while for para or ortho coupling they are perfectly in phase and exhibit constructive QI.…”
mentioning
confidence: 99%
“…The measured single-molecule conductance of Au/p/Au junctions is 0.125 G o (AE 0.006), consistent with calculations and two orders of magnitude higher than the measured conductance of a phenyl ring connected by standard anchoring groups. [14,[29][30] We attribute this conductance peak to charge transport perpendicular to the aromatic ring of the mesitylene molecule.…”
Section: Methodsmentioning
confidence: 89%
“…The single molecule conductance of this Au/p/Au junction is about 0.1 G o , 100-fold more conductive than junctions formed by benzene rings connected by typical standard linkers, for example, thiols or amines. [14,29,30] Our high-resolution STM images show that mesitylene forms a long-range ordered structure on Au(111) (Figure 1 a). A closer look at the STM images (Figure 1 b), as well as the corresponding cross sections (see Figure S1 in the Supporting Information), reveals that mesitylene lies flat on the gold surface.…”
mentioning
confidence: 80%
See 1 more Smart Citation